Message Design Logic on Lecturer @buiramira's TikTok Account - Mujawaroh Annafi; Sri Hastjarjo; Ign. Agung Satyawan (Formosa Journal of Social Sciences (FJSS), 2023)
Social media is growing rapidly, such as Twitter, Facebook, Instagram and TikTok. TikTok is known as an entertainment social media. Various content is presented by creators from different professions. One of them is Padjadjaran University Communication Management Lecturer Ira Mirawati with the TikTok account @buiramira. He made his account as a means to spread informative messages related to final year student activities. Using message design logic theory, this article aims to find out the message design logic on that account. The method used in this research is a qualitative method with case studies. Data collection is done by document study. The results show that the most dominant message design logic is conventional design logic with unifunctional conventional structures, followed by expressive design logic with multifunctional structures, and rhetorical design logic with unifunctional structures